2018
DOI: 10.21111/educan.v2i1.2441
|View full text |Cite
|
Sign up to set email alerts
|

Madrasah, Quality and Strategic Plan

Abstract: This paper aims to understand the the quality improvement of Madrasah as one of the Islamic education institutions of Indonesia, through the construction of strategic plan (renstra) for the development of Islamic education. Madrasah quality must be well managed so that it can realize the goals and noble values of Islamic education. Its missions are actually heavier than public schools because of the broader range of functions and tasks. Its goal as Islamic education institutions includes spiritual competence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The resulting output is to get quality schools in accordance with stakeholder expectations. 55 This study then harmonizes the results of Darda's research which concludes that a good management strategy to improve the quality of madrasah is for example an inventory of main activities, strategy formulation, action plans, and quality learning development procedure schemes 56 . This study also harmonizes the results of a study by Burhanudin et al who concluded that a quality improvement strategy can use two main activities, namely efforts to improve the quality management system which includes (a) focusing on customers; (b) quality improvement; (c) teamwork in implementing quality management.…”
Section: Gaps In Literaturementioning
confidence: 52%
“…The resulting output is to get quality schools in accordance with stakeholder expectations. 55 This study then harmonizes the results of Darda's research which concludes that a good management strategy to improve the quality of madrasah is for example an inventory of main activities, strategy formulation, action plans, and quality learning development procedure schemes 56 . This study also harmonizes the results of a study by Burhanudin et al who concluded that a quality improvement strategy can use two main activities, namely efforts to improve the quality management system which includes (a) focusing on customers; (b) quality improvement; (c) teamwork in implementing quality management.…”
Section: Gaps In Literaturementioning
confidence: 52%
“…In addition, benchmarking the national education system to embody the mission and vision of the country's education requires benchmarking for each educational institution based on specific criteria. These criteria include: (1) providing a holistic education, (2) implementing education processes that promote creativity, democracy, and dialogue, (3) ensuring measurability and observability for better education outcomes, (4) maintaining the professionalism of educators and education personnel, (5) providing adequate facilities and infrastructure, (6) empowering education members through the development of educational management, and (7) continuously improving education quality assurance through evaluation, accreditation, and certification (Darda, 2018).…”
Section: Benchmarking In Educationmentioning
confidence: 99%